Chronic subdural hematoma patients aged 90 years and older. (1st April 2013) - Stippler, Martina; Ramirez, Pedro; Berti, Aldo; MacIndoe, Chamisa; Villalobos, Nicholas; Murray-Krezan, Cristiana
<x xml:space="preserve">Abstract</x> Objectives: The American population above 65 years of age will double by 2050, and more nonagenarians will present to neurosurgeons for treatment for subdural hematomas (SDH), common in the elderly. Healthcare providers, and patients' relatives, often choose treatment when there is little chance of recovery. Hospital mortality is 24% (n = 5) in chronic subdural hematoma (cSDH) patients over 65 years, but there are no studies on cSDH outcomes in patients aged over 90 years. This retrospective study evaluates outcomes in this population. Methods: We reviewed all patients with cSDH between December 2005 and December 2011. We analyzed charts of patients aged 90 years and older. Patient demographics, Glagow Coma Scale (GCS) at presentation, medical co-morbidities, length of stay, disposition, treatment, and radiographic characteristics were abstracted. Results: Twenty-one patients aged 90 or older with 24 admissions for cSDH were identified. Median age was 92 (SD = 2·5); 76% (n = 16) underwent surgery. Median presentation GCS was 14. Disposition to home, rehabilitation facility, nursing home, hospice, or death were not significantly different between conservative and operative groups (P = 0·10), nor was admission GCS (P = 0·59). The size of SDH was significantly (P = 0·02) larger in the operative group. Overall, only 24% (n = 5) of patients were discharged home. Conclusion: Clinical presentation with cSDH is a sentinel event for patients aged 90 years or older; 67% have surgical intervention. Disposition does not vary with surgical or non-surgical treatment. Only 24% of patients of this age group presenting with cSDH return home despite a good admission GCS.